Kemampuan Menemukan Kalimat Utama dalam Paragraf Deduktif dengan Menggunakan Model Pembelajaran Inquiry pada Siswa Kelas V SDI Onekore 6 Kecamatan Ende Tengah Kabupaten Ende - Aloysia Deno (Program Studi Pendidika Bahasa dan Sastra Indonesia, 2020)
The formulation of the problem raised in this study is how is the ability to find the main sentence in a deductive paragraph using the Inquiry learning model for fifth grade students of SD Impres Onekore 6, Ende Tengah District, Ende Regency. This study uses a quantitative approach. The data collection technique used in this research is the test technique. After the data was collected, the data were analyzed using the written test method and then the data were presented formally, meaning that the data were described using numbers. The theory used in this research is the learning evaluation theory and syntactic theory.The results showed that the fifth grade students of SDI Onekore 6 were classified as capable because it was seen from the average value obtained by all sample students was 80.5% and capable students were 16 people with a percentage of 80% and students who were unable as many as 4 people with a percentage of 20%.